Federalism, decentralisation and the liberalisation of business environment in Nigeria (2001)
"This study examines how federal restructuring and decentralisation can be tailored towards the creation of an enabling environment for business in Nigeria. It does this by making a comparative assessment of the business environment in Nigetia; exploring the character of federalism and decentralisation programmes in Nigeria. It also examines the implications of these for governance and the business environment in Nigeria while suggesting decentralisation reforms required to enhance government efficiency and effectiveness as well as improving the business environment. The study noted that decentralization programmes in Nigeria began from the colonial era but have largely taken the form of spatial deconcentration. As a result, they have had the effect of increasing central control and reducing opportunities for citizen participation, and stultified creativity. The restraint in devolving power is attributable to the effort at regime sustenance in the face of limited state legitimacy, the problem of fragile national unity and the prevalence of military dictatorship with its centralizing tendencies. Territorial fragmentation and internal boundary adjustments have resulted in a proliferation of states and local governments; but such levels of government have been without local power that can attract and stimulate participation. Spatial deconcentration has resulted in a bloated states sector, with minimal private sector development, and a suppression of innovative and entrepreneurial energy. Dependence of sub-national units on oil revenue from the centre has been one of the major reasons fur the failure to diversify the economic base of the country. The competition that had characterised inter-state relations under the three and four-region Systems in which derivation was a significant factor of horizontal revenue sharing gave way to political struggles for federation funds. Thus, local spending became completely separated from local resources in the name of even development across the country. The centralisation of resources control and the adoption of a general revenue allocation formula provided no incentive for competitiveness among the various sub-national governments. Decentralisation reforms have become imperative but need to be done democratically. There should be wide spread consultation and negotiation to reach consensus on an ideological base for the envisaged decentralization programme. There should also be very clear institutional arrangement for managing the process, realistic and clear-cut distribution of powers and functions among the various governments based on the principle of subsidiarity with clearly spelt out institutions of horizontal and vertical accountability. The programme should be informed by a more practicalconcern about economic competitiveness, such that the country will be restructured into competing governmental units, providing room for public/private partnership in productive activities at the lower levels, such that would enable the exploration and development of economic potentials of the various states. The current general revenue sharing formula should be reconsidered with a view to promoting competition hand in hand with the drive for equity and accountability. Caution should be taken during the process to avoid fanning the embers of centrifugal forces. Nigeria should borrow ideas from successful decentralisation efforts in other lands. "